Institute for Environmental Security and Environmental Risks in Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The development o fi nsittutionofecological in Kazakhstan is a veryimportantmechanismbecauseoftheproblemsofpolutionofthenaturalenviroment and lowinvestment in precations and liqudationoftheemergencysituations in totheenviromentalsafety. The practice in theinsuranceallowstoconcludethat in Kazakhstan sel fi nsurancedevelopspoorlybecauseofmanyproblems. Currentlytheattentionisfocusedontheproblemsofcoordinationoftherisksinthesphereofthenaturalenviroment and naturalresourceuse.